2001
DOI: 10.1002/ijc.1549
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of loss of heterozygosity in vulval intraepithelial neoplasia (VIN) is associated with invasive vulval squamous cell carcinoma (VSCC)

Abstract: Vulval intraepithelial neoplasia (VIN) is thought to be the premalignant phase of human papillomavirus (HPV)-associated vulval squamous cell carcinoma (VSCC).Various molecular events have been suggested as markers for progression from VIN to VSCC, but loss of heterozygosity (LOH) in vulval neoplasia has rarely been studied in this context. We performed LOH analysis by polymerase chain reaction (PCR) amplification of polymorphic microsatellite markers at 6 chromosomal loci (17p13-p53, 9p21-p16, 3p25, 4q21, 5p14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 18 publications
(22 reference statements)
2
21
0
Order By: Relevance
“…Indeed, few studies have previously examined the genetic changes associated with highgrade VIN using lower resolution techniques. One investigation (Rosenthal et al, 2001) reported that, of 6 loci (3p, 4q, 5p, 9p, 11p and 17p) examined for LOH using microsatellite marker analysis, 3p was the most frequently affected with LOH in 8 of 28 (29%) informative HPV-positive VIN3 samples, comparable to this study. Elsewhere, metaphase CGH was used to analyse the genetic events Reanalysed data from a previous study on cervical carcinomas (Scotto et al, 2008b).…”
Section: Comparison With Previous Studies On Vulval Neoplasiasupporting
confidence: 85%
See 1 more Smart Citation
“…Indeed, few studies have previously examined the genetic changes associated with highgrade VIN using lower resolution techniques. One investigation (Rosenthal et al, 2001) reported that, of 6 loci (3p, 4q, 5p, 9p, 11p and 17p) examined for LOH using microsatellite marker analysis, 3p was the most frequently affected with LOH in 8 of 28 (29%) informative HPV-positive VIN3 samples, comparable to this study. Elsewhere, metaphase CGH was used to analyse the genetic events Reanalysed data from a previous study on cervical carcinomas (Scotto et al, 2008b).…”
Section: Comparison With Previous Studies On Vulval Neoplasiasupporting
confidence: 85%
“…Limited data are available on the genetic alterations associated with VSCC and VIN precursor lesions; previous studies have used microsatellite marker analysis and metaphase comparative genomic hybridisation (CGH) rather than higher resolution arraybased techniques (Pinto et al, 1999;Jee et al, 2001;Rosenthal et al, 2001;Allen et al, 2002;Micci et al, 2003;Bryndorf et al, 2004;Huang et al, 2005). In contrast, the genetic changes associated with CIN and CxSCC have been extensively studied, most recently using array-based methods (Hidalgo et al, 2005;Wilting et al, 2006Wilting et al, , 2009Choi et al, 2007;Kloth et al, 2007;Scotto et al, 2008a, b).…”
mentioning
confidence: 99%
“…LOH autoradiographs from these samples were shown in our previous report. 7 Similarly, samples exhibiting Ͼ50% reduction in the intensity ratio of the VIN-or VSCC-modified androgen receptor alleles compared to unmodified alleles were classed as having skewed X-chromosome inactivation, indicative of a monoclonal origin. Examples are shown in Figure 1.…”
Section: Separation Visualisation and Interpretation Of Pcr Productsmentioning
confidence: 99%
“…These LOH frequencies were known from our previous study. 7 Where identical losses occurred at more than 1 locus in a sample pair, the odds of this occurring were calculated as the product of the probabilities for loss at each locus. The total probability of observing common losses in the different sample groups was calculated as the product of the probabilities of each sample in that group.…”
Section: Probability Analysismentioning
confidence: 99%
See 1 more Smart Citation